(untitled) (Lembaran Ilmu Kependidikan, 2025)
The lack of teacher readiness in dealing with the integration of artificial intelligence (AI) in education is a significant challenge in the era of digital transformation. Teachers are required not only to master technology but also to possess ethical, reflective, and collaborative competencies in applying AI meaningfully. Therefore, this study aims to identify the competencies required of teachers, the challenges of implementing AI in educational settings, and the direction of relevant and sustainable professional development. This study employs a systematic literature review method on 12 selected articles from the Scopus database, based on a search using the keywords ‘Artificial Intelligence’, ‘teacher competence’, ‘AI in education’, and ‘TPACK’ in English-language articles published between 2020 and 2025. The articles were analysed thematically to explore the interrelationships between teacher competencies, challenges, and development strategies. The analysis results highlight the importance of mastering AI literacy, data management skills, and technology-based pedagogical abilities. The main challenges identified include ethical constraints, infrastructure limitations, resistance to change, and insufficient training. This study recommends the AI-TPACK approach, design thinking, and a growth mindset as a framework for adaptive and future-oriented teacher development.